Analisis Pencapaian Dan Perbaikan Target Overall Equipment Efectiveness (OEE) Pada Mesin Injection - Supriyati Supriyati; Ade Nurul Hidayat (Prosiding Sains dan Teknologi, 2022)
A manufacturing company is a company that carries out a production process to produce a product. The company was founded with the purpose of making a profit or profit, to achieve profit, need to take steps to maximize equipment/machinery so that efficiency increases, quality improvement so that it has a positive impact on customer satisfaction. Product quality and engine efficiency/OEE have a relationship, if product quality is low, it results in low OEE. To determine the performance of a machine in an injection company, it is necessary to measure the OEE value. The results of the analysis show that OEE has not yet reached the target. The most influential factors are the low availability value due to dandori process, material change, mould repair, and damage to the robot that requires long repair time. Improvements were made not only on availability, but to maintain and improve, improvements were made to the OEE component, namely the performance and Quality ratio. The improvement results show a reduction in availability time, a decrease in silver defects in the quality ratio and an increase in performance with improved cycle time. Keywords: TPM, OEE, Availability, Performance, Quality